The public-private sector gender wage differential: evidence from matched employee-workplace data - Monojit Chatterji; Karen Mumford; Peter N. Smith (Institute for the Study of Labor (IZA), 2007)
Using new linked employee-workplace data for Britain in 2004, we find that the nature of the public private pay gap differs between genders and that of the gender pay gap differs between sectors. The analysis shows that little none of the gender earnings gap in both the public and private sector can be explained by differences in observable characteristics. Decomposition analysis further reveals that the contribution of differences in workplace characteristics to the public private earnings gap is sizeable and significant. Whilst the presence of performance related pay and company pension schemes is associated with higher relative earnings for those in the private sector, an important workplace characteristic for the public private pay gap is the presence of family-friendly employment practices. Increased provision is especially associated with higher relative earnings in the public sector for women.
Keywords: J3; 330; Public sector earnings; gender; gap; family friendly; decomposition; Lohnstruktur; Öffentlicher Sektor; Privatwirtschaft; Lohndifferenzierung; Geschlechterdiskriminierung; Frauenarbeitslohn; Dekompositionsverfahren; Großbritannien